Atorvastatin affects C-reactive protein levels in patients with coronary artery disease - Karaca, I; Ilkay, E; Akbulut, M; Yavuzkir, M; Pekdemir, M; Akbulut, H; Arslan, N (Taylor & Francis Ltd, 2003)
Background: Elevated levels of C-reactive protein (CRP) are considered to be one of the indicators of poor prognosis in coronary artery disease (CAD). The aim of this study was to evaluate anti-inflammatory effects of atorvastatin in patients with CAD by measuring serum CRP levels. Methods: After measuring the baseline levels of CRP and lipid fractions, the patients were divided into two groups. In Group A (n = 46), atorvastatin (20 mg/day) was administered in addition to classic antianginal treatment (beta-blocker, nitrate and aspirin). In Group B (n = 32), the usual antianginal treatment was continued. Following 4 weeks of treatment the same measurements were repeated. Results: In Group A, CRP decreased from 20.3 mg/dl (95% Cl, 9-31.8) to 10.8 mg/dl (95% Cl, 2.7-18.9) (p < 0.001). In Group B, CRP decreased from 17 mg/dl (95% Cl, 13.1-21) to 12.8 mg/dl (95% Cl, 9.7-15.9) (p < 0.01). The decrease in group A was more than in group B (p = 0.003). Conclusions: In patients with CAD, atorvastatin exerted an anti-inflammatory effect represented by decreasing CRP levels. This effect was independent of the change in low density lipoprotein cholesterol (LDL-C) or high density lipoprotein cholesterol (HDL-C) levels.
Keywords: atorvastatin; coronary artery disease; C-reactive protein; inflammation